Simple, Fast, and Low Cost Judicial Principles in Split Trials - Dian Dwi Kusuma Astuti (Universitas Negeri Semarang, 2021)
Split trial in practice collides with the principle of justice which is simple, fast, and low cost. The purpose of this study is to determine the application of the principle of simple, fast, low cost justice and to find out the ideal or effective concept of applying the principle of simple, fast, low cost justice in a split trial. The approach used is a qualitative approach. This type of research is juridical empirical. The data used are primary data and secondary data. Data obtained through interviews and literature study. The results showed that the implementation of the principle of simple, fast, low cost in a split trial is that the principle is not fulfilled optimally. Merging the examination process at the trial in the case of splitsing, can streamline the split trial by keeping the case files separate.